Hubungan Self Efficacy, Peran Bidan, Dan Dukungan Suami Terhadap Pemeriksaan Pap Smear Pada PUS Di Rumah Sakit Tugu Ibu Depok : The Relationship between Self-Efficacy, the Role of Midwives, and Husband's Support for Pap Smear Examinations at EFA at Tugu Ibu Hospital, Depok - Widhiyanti, Retno (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Cervical cancer is still an issue that is often discussed in the world of health. Cervical cancer is the most common malignant tumor found in the reproductive organs. All women are at risk of suffering from this cancer especially women who are sexually active. Pap smear is a type of examination that can be done to identify cervical cancer. The prevalence of cancer in women in Indonesia in 2021 is 30.8% for breast cancer, 17.2% for cervical cancer, and 7% for ovarian cancer. The purpose of this study was to determine the relationship between self-efficacy, the role of midwives, and husband's support for pap smear examinations at PUS at Tugu Ibu Hospital in Depok in 2022. Methods: This type of research used descriptive analytic with a cross-sectional approach. The sampling technique used is simple random sampling with a total of 53 respondents. Results: The results of the study showed that there was a relationship between self-efficacy (p-value 0,001); the role of the midwife (p-value 0,026); and husband's support (p-value 0,008) for pap smear examination in PUS at Tugu Ibu Hospital. Discussion: The conclusion is that there is a relationship between self-efficacy the role of midwives, and husband's support for pap smear examination at PUS at Tugu Capital Hospital in Depok City in 2023. Suggestions for couples of childbearing age to be able to increase self-efficacy by increasing understanding of the benefits and importance of Pap Semar examination through asking to health workers, attending counseling classes, health seminars or reading from trusted sources.